On the inhibitory actions of baclofen and gamma-aminobutyric acid in rat ventral midbrain culture - Jarolimek, Wolfgang; Misgeld, Ulrich (The journal of physiology, 1992)
1. Whole-cell voltage-clamp recordings were used to study the effects of (-)-baclofen and of gamma-aminobutyric acid (GABA) on neurones cultured from the ventral midbrain of embryonic rats. 2. Baclofen induced an outward current (IBac) at a holding potential of -60 mV. The maximal current was 80 pA, and half-maximal current was evoked by 5 microM-baclofen. The proportion of cells affected by baclofen was greater in 25-day-old cultures than in 14-day-old cultures. 3. IBac was blocked by barium (1 mM), and it reversed polarity at a potential that changed according to the Nernst equation when the extracellular potassium concentration was changed. The reversal potential was not different when recording electrodes contained caesium instead of potassium. 4. GABA (10-20 microM), in the presence of picrotoxin (50 microM) and bicuculline (50 microM), also evoked a small potassium current at -60 mV. There was no correlation between the amplitude of the potassium current caused by GABA and that caused by baclofen measured in the same neurones. 5. Spontaneous synaptic currents (up to hundreds of picoamps) were observed that were blocked by picrotoxin (20 microM; IPSCs) or by 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX, 10 microM; EPSCs); the amplitude and frequency were strongly reduced by baclofen and by GABA. 6. Spontaneous synaptic currents of lower amplitudes (up to 60 pA) remained in the presence of tetrodotoxin. IPSCs (blocked by picrotoxin, reversal at -50 mV) and EPSCs (blocked by CNQX, reversal at 0 mV) were reduced in frequency by baclofen. GABA, in the presence of bicuculline and picrotoxin, had a similar effect on the EPSCs. This action of baclofen persisted in barium (1 mM), and was observed as readily in cells cultured for 14 days as those cultured for 25 days. 7. Some spontaneous synaptic currents remained in the presence of tetrodotoxin and cadmium (100 microM). Their frequency was reduced by baclofen. The effectiveness of baclofen was greater on cells that had been longer in culture. 8. It is concluded that activation of GABAB receptors has two main effects on neurones cultured from rat ventral midbrain. These are potassium conductance increase, and inhibition of the spontaneous release of GABA and excitatory amino acids; both effects can be observed in tetrodotoxin and cadmium.
Gesehen am 26.04.2021